Integrating sustainable development goals in English language and literature teaching - Cordova, Monique (Frontiers in Education, 2024)
Teaching English provides the possibility for raising students' awareness of global issues. By bringing relevant global issues into the classroom, teachers can provide students a rich array of activities and topics that increase their engagement with diverse cultures, issues of local as well as global importance. This study explored the integration of the Sustainable Development Goals in English language and literature teaching in a state university laboratory school in the Philippines. It focused on the learning experiences and feedback of pre-service teachers and junior high school students on the integration. The phenomenological research design, the interview and focus group discussion were utilized. For a concise description of themes and patterns relevant to the phenomenon, thematic analysis was done after the data gathering. Four dominant themes were revealed in the learning experiences of the teaching interns during the study: Designing for Concrete Action; Applying the Interdisciplinary and Contextualized Approach; Nurturing a Participatory Attitude; and Fostering Personal Accountability. The feedback of the learners on the SDG integration included themes such as Empowerment to Take Initiative, Gaining Meaningful Learning, and Developing a Whole-School Approach. The Integration of SDGs in the English classroom provided a range of benefits for both pre-service teachers and students. Students were given the tools to expand their learning and develop the capacity to proactively address a variety of problems. They were encouraged to view these issues as their own, fostering a sense of ownership and purpose, rather than merely striving for knowledge and comprehension. This is a provisional file, not the final typeset article When teachers aim to give classroom activities that inspire students to learn more about the broader world and take into consideration how events affect their lives, the learning becomes meaningful and relevant. English teachers, in many parts of the globe, have spearheaded transformative shifts in education. Communication tasks, collaborative work, learner autonomy, project work, are all grounded in a concept of learning that recognizes students as engaged participants and thinkers, instead of mere passive absorbers of knowledge.